Early Postresuscitation Hypotension Is Associated With Increased Mortality Following Pediatric Cardiac Arrest* - Alexis Topjian; Benjamin French; Robert M. Sutton; Thomas Conlon; Vinay Nadkarni; Frank W. Moler; Jay B. Dean; Robert A. Berg (2014)
To describe the association of systolic hypotension during the first 6 hours after successful resuscitation from pediatric cardiopulmonary arrest with in-hospital mortality.Retrospective cohort study.Fifteen children's hospitals associated with the Pediatric Emergency Care Applied Research Network.Patients between 1 day and 18 years old who had a cardiopulmonary arrest, received chest compressions more than 1 minute, had a return of spontaneous circulation more than 20 minutes, and had a systolic blood pressure documented within 6 hours of arrest.None.Three hundred eighty-three patients had complete data for analysis. Patients with a documented minimum systolic blood pressure less than fifth percentile for age and sex within the first 6 hours following return of spontaneous circulation were considered to have early postresuscitation hypotension. Two hundred fourteen patients (56%) had early postresuscitation hypotension. One hundred eighty-four patients (48%) died prior to hospital discharge. After controlling for patient and cardiopulmonary arrest characteristics, hypotension in the first 6 hours following return of spontaneous circulation was associated with a significantly increased odds of in-hospital mortality (adjusted odds ratio = 1.71; 95% CI, 1.02-2.89; p = 0.042) and odds of unfavorable outcome (adjusted odds ratio = 1.83; 95% CI, 1.06-3.19; p = 0.032).In the first 6 hours following successful resuscitation from pediatric cardiac arrest, systolic hypotension was documented in 56% and was associated with a higher rate of in-hospital mortality and worse hospital discharge neurologic outcomes.